Colaboration Strategy on Prevention and Handling of Sexual Violence on Adolescents between Indonesian Family Planning Association - Saudah, Noer; Lestari, Indah; Abidin, Chasiru Zainal; Delshitawati, Catur; Zamroni, Asroful Hulam (STIKes Patria Husada Blitar, 2025)
The increase in adolescent sexual activity puts adolescents at risk of experiencing sexual violence, including on campus. Several universities have made efforts to prevent and address sexual violence on campus. This study aimed to compile a Collaboration Strategy of college with Indonesian Family Planning Association with College in East Java in the prevention and handling of Sexual Violence among adolescents. The design qualitative method with a Focus Group Discussion approach. This focus group discussion was attended by prevention and handling of Sexual Violence on adolescents’ experts from Indonesian family planning association, and lecturers from 4 universities in East Java, namely from Jember University, Bina Sehat PPNI Mojokerto University, Institute of Health Science Ar-Rahmah Gempol Pasuruan and health sciences Surya Mitra Husada Kediri Kediri. The sampling technique used purposive sampling with 4 informants. Triangulation was carried out on 3 informants from Indonesian family planning association. The research instrument was the researcher himself and the Focus Group Discussion guidelines. The data analysis used data reduction, data presentation, data verification, and data validity testing. The informant's university of origin stated that it had implemented efforts to prevent and handle sexual violence against adolescents and had reported the implementation to Belmawa Information System. The obstacles faced were the limited number of expert human resources, partners, and information media. The recommendation from the Focus Group Discussion was a collaborative strategy between Universities and Indonesian family planning association in efforts to prevent and handle sexual violence against adolescents on campus.